MOMAC: a SAXS/WAXS laboratory instrument dedicated to nanomaterials. Issue 5 (9th September 2016) - Taché, Olivier; Rouzière, Stéphan; Joly, Philippe; Amara, Mohamed; Fleury, Blaise; Thill, Antoine; Launois, Pascale; Spalla, Olivier; Abécassis, Benjamin
Abstract : An in‐house‐constructed SAXS/WAXS instrument dedicated to the study of a wide range of nanomaterials is described. The different parts of the instrument are described in detail, along with several calibration standards and examples from recent research. Abstract : This article presents the technical characteristics of a newly built small‐ and wide‐angle X‐ray scattering (SAXS/WAXS) apparatus dedicated to structural characterization of a wide range of nanomaterials in the powder or dispersion form. The instrument is based on a high‐flux rotating anode generator with a molybdenum target, enabling the assessment of highly absorbing samples containing heavy elements. The SAXS part is composed of a collimation system including a multilayer optic and scatterless slits, a motorized sample holder, a vacuum chamber, and a two‐dimensional image‐plate detector. All the control command is done through a TANGO interface. Normalization and data correction yield scattering patterns at the absolute scale automatically with a q range from 0.03 to 3.2 Å −1 . The WAXS part features a multilayer collimating optic and a two‐dimensional image‐plate detector with variable sample‐to‐detector distances. The accessible q range is 0.4–9 Å −1, ensuring a large overlap in q range between the two instruments. A few examples of applications are also presented, namely coupled SAXS/WAXS structure and symmetry determination of gold nanocrystals in solution and characterization of imogolite nanotubes and iron‐filled carbon nanotube samples.